2021
DOI: 10.1002/stc.2817
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive bidirectional dynamic response control of offshore wind turbines with time‐varying structural properties

Abstract: Wind, wave and seismic loading induced excessive vibration of offshore wind turbines (OWTs) impairs the wind turbine energy output and escalates its fatigue damage. The present study proposes a three-dimensional adaptive pendulum tuned mass damper (3D-APTMD) to control the bidirectional dynamic responses of monopile OWTs exposed to combined wind, wave, seismic loading, and time-varying structural properties. In terms of the proposed adaptive tuning algorithm, the natural frequency and damping property of the 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…where v nf and v ns are the absolute generalized velocities of nacelle in F-A and S-S directions, respectively. As shown in Figure 3, the absolute generalized displacements of the infnitesimal unit dr of the blade in the Oxyz coordinate system can be obtained from equation (2) and the local coordinate transformation of the blade as x bej � x ns + r sin θ bj + q j φ bej cos θ bj ,…”
Section: Generalized Absolute Displacement and Velocitymentioning
confidence: 99%
See 1 more Smart Citation
“…where v nf and v ns are the absolute generalized velocities of nacelle in F-A and S-S directions, respectively. As shown in Figure 3, the absolute generalized displacements of the infnitesimal unit dr of the blade in the Oxyz coordinate system can be obtained from equation (2) and the local coordinate transformation of the blade as x bej � x ns + r sin θ bj + q j φ bej cos θ bj ,…”
Section: Generalized Absolute Displacement and Velocitymentioning
confidence: 99%
“…Te ofshore wind turbine (OWT) has become more popular in recent years due to advantages of being a cheap energy source, less visual impact, low noisy problem, and without land requirement [1]. Taller and slender large-megawatts OWTs have been constructed ofshore [2] to capture more energy. However, the steel OWT structure has a long vibration period and light damping which make it more vulnerable to signifcant vibrations caused by wind or waves [3].…”
Section: Introductionmentioning
confidence: 99%
“…The 3d-PTMD is a passive controller and it might lose its effectiveness in the presence of system and environmental variations. Therefore, Sun et al [22] proposed using a three-dimensional adaptive pendulum TMD (3d-APTMD) to control the bi-directional responses of the tower under time-varying structural properties. The authors compared the effectiveness of the 3d-APTMD with 3d-PTMD and concluded that the 3d-APTMD is more effective in reducing the tower vibrations in the presence of structural property variations.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on STMDs compare the semi‐active dampers with their passive counterparts and demonstrate the extraordinary capacity of these devices. Additionally, the semi‐active protection based on variable stiffness and damping ratio has been recently proposed for the multi‐hazard control of offshore wind turbines 64,65 . However, no specific STMD has been suggested, to the best of our knowledge, for multi‐hazard purposes applied to buildings.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the semi-active protection based on variable stiffness and damping ratio has been recently proposed for the multi-hazard control of offshore wind turbines. 64,65 However, no specific STMD has been suggested, to the best of our knowledge, for multi-hazard purposes applied to buildings. Additionally, these devices require competent control algorithms governing their properties variation, and reliable systems of sensors and frequency identification.…”
mentioning
confidence: 99%